2015
DOI: 10.3109/00207454.2015.1074225
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of subthalamic oscillatory activity in parkinsonian akinetic-rigid type and mixed type

Abstract: The STN βFB oscillatory neurons correlate with parkinsonian rigidity-bradykinesia. The high proportion of βFB oscillatory neurons found in the AR type of PD is indirect evidence for their importance in generating motor impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…40,41 In our previous study, βFB has also been directly correlated with rigidity. 16 In other studies, a direct relationship between basal ganglia oscillations and tremor has been found. 22,42 The TFB oscillations are tremor coherent in more than 50% of STN neurons.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…40,41 In our previous study, βFB has also been directly correlated with rigidity. 16 In other studies, a direct relationship between basal ganglia oscillations and tremor has been found. 22,42 The TFB oscillations are tremor coherent in more than 50% of STN neurons.…”
Section: Discussionmentioning
confidence: 78%
“…As described in previous studies, 16,23 microelectrode recordings were performed during targeting using the Microguide system Pro (AlphaOmega Engineering, Nazareth, Israel) with patients at rest as a general step in the targeting procedure. Briefly, a tungsten microelectrode with tip size 10-20 μm and resistances from 0.3 to 0.5 MΩ at 1000 Hz (Alpha Omega Engineering, Nazareth, Israel) was used.…”
Section: Microelectrode Recordingmentioning
confidence: 99%
See 1 more Smart Citation
“…While dopamine loss is, in some way, related to the expression of tremor, this parkinsonian sign is often less sensitive to dopamine replacement therapy than the other parkinsonian signs, and not strongly related to beta-band power in LFP signals recorded in the basal ganglia [163].…”
Section: Pathophysiology Of Parkinsonism and Dystoniamentioning
confidence: 99%
“…It is thought that the overly strong beta-band LFP oscillation indicates that desynchronization processes of neurons within the circuitry fail in PD, which may contribute to the hypokinetic features of the disease. This has led to the proposal that beta-band LFP oscillations are antikinetic and strongly correlated with rigidity and bradykinesia [163], while gamma-band oscillations (a sign of desynchronization) are thought to be prokinetic [162]. Beta oscillations are viewed as normal for the resting or Bidling^state; their reduction with movement onset may play a role in allowing movement to take place.…”
Section: Pathophysiology Of Parkinsonism and Dystoniamentioning
confidence: 99%